Collaborative system for web seminars, distance learning sessions and virtual labs in biomedicine. (1st January 2013) - Landro, Daniele; Gasperis, Giovanni De; Macchiarelli, Guido
In recent years, there has been a growing interest about new techniques for information exchange in medical context. Academic communities need a collaborative portal with a certain degree of interactivity between speaker and audience to provide new learning opportunities. The objective of the test program is to provide a modular and user-friendly web portal that allows the exchange of scientific information and takes into account only the centrality of four essential elements: teachers, learners, the learning process and the learning content. This collaborative system also contains 3D learning objects to simulate highly interactive virtual laboratories. More than 300 biomedical students were enrolled to carry out the assessment of the platform. Students who completed the web-based module left positive feedback and demonstrated good overall satisfaction with the assessment. The collaborative portal revealed an acceptable teaching alternative to integrate face-to-face instruction with thematic webinars.